Is it possible to mitigate greenhouse gas emissions in pastoral ecosystems of the tropics? - Reid, Robin S.; Thornton, Philip K.; McCrabb, G.J.; Kruska, Russell L.; Atieno, F.; Jones, Peter G. (Springer, 2004)
Climate change science has been discussed and synthesized by the world's best minds at unprecedented scales. Now that the Kyoto Protocol may become a reality, it is time to be realistic about the likelihood of success of mitigation activities. Pastoral lands in the tropics hold tremendous sequestration potential but also strong challenges to potential mitigation efforts. Here we present new analyses of the global distribution of pastoral systems in the tropics and the changes they will likely undergo in the next 50 years. We then briefly summarize current mitigation options for these lands. We then conclude by attempting a pragmatic look at the realities of mitigation. Mitigation activities have the greatest chance of success if they build on traditional pastoral institutions and knowledge (excellent communication, strong understanding of ecosystem goods and services) and provide pastoral people with food security benefits at the same time.